PENGEMBANGAN MODEL LAYANAN INFORMASI DENGAN TEKNIK SYMBOLIC MODEL DALAM MEMBANTU MENGEMBANGKAN KEMANDIRIAN BELAJAR ANAK USIA SEKOLAH DASAR DI KECAMATAN KOTA KUDUS TAHUN PELAJARAN 2014/2015 - Lestari, Indah; Hidayati, Richma; Zamroni, Edris (Universitas Muhammadiyah Metro, 2015)
Abstract: This study was motivated by the phenomenon of independent learning elementary school children who tend to be low. This can be observed from the tendency of primary school age children dependent on parents, friends and tutors in the homework, cheating when it replicates and mimics the work of friends. The purpose of this study was to develop a model of information services with symbolic techniques to develop independent learning model of primary school age children. The results showed that the value of t obtained figures on chances of error 0.000 9.682 less than the chance of error (p) = 0.05 or in other forms 0.000 <0.05, which means significant. Furthermore, a different test showed that the average post-test bigger with 59.26 value compared with the value of the pre-test of 49.96. Thus, the alternative hypothesis that reads information service model by using symbolic models can significantly improve student learning independence supported or accepted.Keywords: Independence learning, information services, symbolic models